Radular ultrastructure of South American Ampullariidae (Gastropoda: Prosobranchia) - Martin, Stella Maris (2007)
The radula of five species of South American Ampullariidae was analysed by Scanning Electron Microscope (SEM) with the purpose of enlarging new studies on the systematic of this family. The studied species were Pomacea canaliculata (Lamarck, 1822), Pomacea scalaris (d'Orbigny, 1835), Pomella (P.) megastoma (Gray, 1847), Asolene A.) platae (Maton, 1809) and Felipponea neritiniformis (Dall, 1919). The central tooth shows different attributes which provide the means for generic determination; the analysis of the central tooth, the lateral and marginal ones by SEM adds further information for species differentiation.